Textual Indications (Dalālāt Alfāz) In The Foundations Of Islamic Jurisprudence Comparative Analysis Of The Hanafī And The Mutakallimūn Schools - Mosa alblezi, Mohd Aderi Che Noh (International Journal of Advanced Science and Technology, 2020)
This paper undertakes a discussion about textual indications (dalālāt alfāz) found in the science of usūl al-fiqh (foundation of jurisprudence). This will be done through considering the perspectives of two jurisprudence groups; namely, the Hanafī School and the Mutakallimūn, who are synonymous to the Shāfi‛ī School, the Mālikī School and the Hanbalī School. It will be argued that the dalālāt alfāz is critical for the basis of Islamic legal interpretation from its primary sources, the Qur’ān and the Sunnah. This is because there is a considerable significance attributed to this branch of usūl al-fiqh, i.e. to achieve a comprehension of intended meanings of the words and expressions within the textual sources; there is a prerequisite, the knowledge of dalālāt alfāz. Through this knowledge the main two groups were at variance in their methodology, interpretation and application of the law, which is what this article will discuss and analyse.